Comparision between self-reported hypertension and casual blood pressure and presence of cardiovascular risk factors among health workers of Bauru and Jau cities - Louzada, Juliana C. A.; Andrade, Rafael M.; Dionísio, Evandro J.; Barel, Matheus; Monteiro, Henrique L.; Amaral, Sandra Lia (Medicina (Ribeirao Preto), 2010)
Model: Prevalence study. Objectives: To evaluate the presence of self-reported hypertension to compare with blood pressure measurements. Besides, this work investigated health information level of workers and if the job position has any influence on blood pressure (BP). Methods: This study evaluated 349 health workers (44±10 years old) from Bauru and Jau cities, who answered some questions about history of health condition, use of medicines, past surgeries as well as social, scholar and physical conditions and had their blood pressure measured. Each subject selfreported as normotensive or hypertensive. Values of systolic >≥ 140 mmHg and/or diastolic PA >-90 mmHg were considered elevated. Among the health workers evaluated, 198 were submitted to thropometric and biochemical evaluations. Values are presented as means ± SD and frequency of distribution. It was used T-student test (p<0.05). Results: From all workers evaluated only 16% self-reported as hypertensive, which 56% presented high BP, however 91% used to take antihypertensive medicines. Among the 84% who self-reported as normotensive, 24% presented high BP and 8% used to take medicines. Although most of the employees of each section self-reported as normotensive, more than a half presented high BP and which was more common in the health’s section (76.3%). Conclusion: These results suggest that besides the majority of the employees self-reported as normotensive, an elevated number of health workers presented high blood pressure and used to take medicines appropriately,which indicates that they did not have enough knowledge about their health. Furthermore, it was observed that Health Section presented the higher blood pressure values.